Peran Guru PAK dalam Pengembangan Potensi Siswa UPT SDN 065011 Medan Selayang Melalui APE - Heri Endang Wani (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This study aims to examine the role of teachers in improving students' potential, with a focus on aspects of learning and character development. The role of teachers is very important in supporting the development of various student potentials, both in terms of academics and character, both of which contribute to students' readiness to face future challenges. This study uses a qualitative literature method. Data were collected through document analysis related to learning programs and extracurricular activities. The results of the study indicate that teachers play a role in identifying and exploring students' potential through creative and adaptive learning methods. The conclusion in this study shows that developing students' character by instilling moral values, discipline, and responsibility has an impact through direct role models, effective communication, and positive interactions between teachers and students. This study suggests the need for ongoing training for teachers so that they can be more optimal in developing students' academic and character potential.